Central PABX virtual em Raspberry Pi 3 modelo b - Andrade, Ailton Carlos de (2018)
With the advancement of computing, especially the use of computer networks in the follow-up of telecommunications, the use of specific technologies for voice communication has become increasingly expensive and obsolete, even with this advance the need to reduce costs for small consumers is necessary because of the high costs in deploying new technologies. As an alternative, "VoIP" technology is emerging, which refers to the use of computer-based voice communications, coupled with low-cost hardware (Raspberry Pi), a high-value processing component for a lowcost platform (free of charge). In this sense, this work analyzes the performance of a PBX under "hardware" based on practical tests of performance and use of quality parameters to determine the quality of the results obtained. The results tremendous performance for small switches with great communication quality and low cost of deployment and maintenance. It is concluded that one can make use of the reported model as an alternative applied to small networks.